"V" is for vengeance - Grafton, Sue (Grafton, Sue. Kinsey Millhone mysteries., 2011)
California PI Kinsey Millhone investigates the death of Audrey Vance, a woman she helped arrest for shoplifting, and antagonizes just about everyone, including Audrey's fiancé, several loan sharks, a stone-cold killer, and a hapless burglar who knows more than is healthy for him.